Analysis of channel integration quality on channel attributes towards customer purchase preference fore coffee Indonesia - Ramadhan, Mohammad Nugraha; Nasution, Reza Ashari (Journal of Business and Management, 2020)
Abstract. Customer demand on purchase experience across all integrated channel has driven retailer industries, especially food and beverage retailers to make a technological advancement of channel integration through omnichannel retailing to remain competitive. Channel-service configuration, and channel integration quality is the main aspects regarding the customer engagement of the omnichannel strategy. However, development of omnichannel practice on the food and beverage retailing industries drives customer confusion to choose their channel preference regarding the purchase stage. Despite the new seamless customer experience given, omnichannel practice has a big cost to develop it. This research aimed to analyse the key driver regarding the channel attributes, and impact of customer experience towards customer channel purchase preference of Fore Coffee Indonesia by identifying the key drivers that affect the perceived quality, price, and convenience. The data of this research is obtained using an online questionnaire through 200 respondents and further be analysed using SEM-PLS. This research findings based on the data analysis shows that channel attributes and channel experience have a positive relationship towards channel purchase preference. Channel experience has the highest impact influencing customer purchase preference on the omnichannel platform. This research findings are expected to provide a broader perspective to food and beverage retail industry that managed to make a technological advancement of omnichannel strategy, where channel attributes and channel experience should be considered to gain improvement for the company. Whereas, content consistency, process consistency, and breadth of channel-service choice also need to be maintained to achieve a consistent channel attributes among all available channel.Keywords: Omnichannel; Channel Choice Preferences; Integration Quality; Channel-service Configuration; Channel Experience; Channel Attributes